Antioxidant Activity Test of The Aqueous Fraction of Tetanus Leaves (Leea aequata L.) Using The DPPH Method - Siregar, Nurhakiki; Bangar, Roy Indrianto; Kaban, Vera Estefania; Simanjuntak, Nerly Juli Pranita (CV. Nusantara Scientific Medical, 2025)
Antioxidants play a crucial role in neutralizing free radicals, thereby helping to prevent cell damage and maintain overall health. This study aims to evaluate the antioxidant activity of the aqueous fraction of Tetanus (Leea aequata L.) leaf extract using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The extraction process was carried out through maceration using ethanol as a solvent, followed by aqueous fractionation. Antioxidant activity was measured based on the extract’s ability to scavenge DPPH free radicals, expressed as the IC₅₀ value. The results showed that the aqueous fraction of Tetanus leaf extract exhibited high antioxidant activity, with an IC₅₀ value of 30.23 mg/L. The total phenolic and flavonoid contents in the aqueous fraction were 460.70 mg GAE/100g and 12,621.14 mg QE/100g, respectively. These findings align with pre vious studies indicating that the ethanolic extract of Leea angulata leaves also possesses strong antioxidant activity with a similar IC₅₀ value. Therefore, the aqueous fraction of Tetanus leaf extract has the potential to be an effective natural antioxidant source and can be further developed as a raw material for health supplements or pharmaceutical products.